BEFORE AND AFTER M&A: FINANCIAL ANALYSIS OF IDX COMPANIES - Jaya Maharani, Junita; Permatasari, Ditya; Dwi Setyaningsih, Nina (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
Mergers and acquisitions are strategies often used by companies to strengthen their business position and improve financial performance. This study focuses on identifying differences in corporate financial performance that may arise before and after mergers and acquisitions. using various financial ratios as measurement tools. This study adopts a quantitative approach with a descriptive focus. The data source is from the Indonesia Stock Exchange (IDX), and the research object includes companies involved in mergers and acquisitions during the period 2015–2020. Sample selection was carried out using purposive sampling based on specific criteria, resulting in 21 companies as samples. Data analysis was conducted using the Paired Sample T-Test and Wilcoxon Signed Rank Test with the assistance of SPSS version 25. The findings of this study reveal that there has been a significant change in CR, DER, TATO, EPS, NPM, ROA, and ROE ratios after mergers and acquisitions, while the DAR ratio did not experience significant changes. Based on these findings, mergers and acquisitions can be concluded as an effective strategy in improving a company's financial performance.